Degradation of betaine aldehyde dehydrogenase transgenic maize BZ-136 straw and its effects on soil nutrients and fungal community - Liu, Xuesheng; Zeng, Xing; Zhu, Yuhang; Wang, Wei; Huang, Siqi; Qiao, Xinxin; Wang, Zhenhua; Di, Hong; Qu, Juanjuan (Frontiers in Microbiology, 2023)
This study aims to investigate the straw degradation of BADH transgenic maize BZ-136 and its effects on soil chemical properties, fungal community composition, community diversity and ecological function compared to non-transgenic maize Zheng58 straw. The degradation experiments of BZ-136 straw were carried out under a simulated burying condition with saline-alkali soil for 210 days. The results showed that the degradation rate of C and N of BZ-136 straw was significantly faster than that of Zheng58 in the early stage (p < 0.05). Compared to Zheng58, the straw degradation of BZ-136 increased the soil available N, total P, and available P in the early stage (p < 0.05). The straw degradation of BZ-136 increased the OTU number of soil fungal community by 127 (p < 0.05) at day 60, and increased Chao1 and Shannon index at day 60 and 180 (p < 0.05). The degradation rate of C and N in BZ-136 straw was higher than that in Zheng58 at early stage, which led to the phased increase of soil AN and TP contents, and the obvious changes of RA of some genera and guilds.